Equity research delta air lines, inc. - shaping a powerful industry - Silveira, Tiago Jesus (2021)
This equity research report looks to provide context to an equity valuation of US-based airline Delta Air Lines, Inc. (DAL:NYSE). The report goes over the past performance of the Delta and its US-based peers while providing some insights on the company's operation. Afterwards, it reflects on the current industry conditions, where the COVID-19 pandemic takes the centre stage on the analysis. Finally, the report identifies future trends for the US airline market.